Avaliação de políticas públicas voltadas à educação superior: o caso do Programa Universidade para Todos (PROUNI) - Barrozo Filho, José Liberato (2019)
The University for All Program (PROUNI) is an important Public Policy, affirmative in nature, aimed at facilitating access to higher education of social strata with less educational,economic and cultural opportunities. A research was designed to obtain clues about PROUNI's results and thus to allow a judgment on the federal program. Such activity approaches the idea of ​​ex-post-facto evaluation, whose function is to provide clarification to society about its relevance or provide social accountability. To that end, two studies were developed to compare PROUNI users with non-users in five different attributes: (i) average training time, (ii) quality of learning, (iii) level of satisfaction with training and (v) level of employability. In the first study, secondary data were used of 924 students who graduated from the undergraduate courses at a Higher Education Institution, while the second study used primary data from the application of a Questionnaire for Egresses in a sample of 88 former students. The results of the comparative analysis between PROUNI users and non-PROUNI users through the ANOVA Test and the Chi-Square Test demonstrated that: (i) PROUNI users presented higher Learning Quality than their non-users peers [F = 13,749 ; p <0.01]; (ii) PROUNI users presented higher Institutional Impact than their non-users peers [F = 4,528; p <0.01]; (iii) PROUNI users presented less training time than their non-users peers [F = 12,055 (p <0.01); (iv) PROUNI users showed satisfaction with the training received and acknowledged the effectiveness of this, [χ 2 (1; 86) = 0.67, p > 0.01]; (v) PROUNI users showed a greater desire to enter the labor market immediately, in order to generate income for their families through professional practice, unlike non-users of PROUNI, whose difference was captured by the Chi- Square [χ 2 (1; 86) = 6.64; p < 0.05].